A influência da adição de MgH₂ em Mg visando a aplicação em tanques de armazenagem de hidrogênio - Chanchetti, Lucas Faccioni (Universidade Federal de São Carlos, 2018)
Magnesium Hydride is a promising material for Hydrogen storage, due to its high capacity, excellent reversibility and low cost of metallic magnesium. High energy ball milling is the main technique for obtaining Mg with reaction kinetics adequate to H2 storage applications. It however possesses high energetic cost and low productivity, besides inflicting air sensitivity, raising processing costs. Previous studies demonstrated that the incorporation of 5% MgH2 to Mg improves its activation kinetics with reduced milling times. In this work, we evaluated the effect of the addition of increasing MgH2 contents to Mg on its activation kinetics and in characteristics of interest for storage tanks, such as air resistance, cyclability and thermal conductivity. Commercial Mg plates were extensively cold rolled, followed by a short ball milling step with addition of hydride. Part of the resulting material was compacted, and air exposed for 1 month. The hydrogen sorption properties were evaluated with a Sieverts-type apparatus and microstructural characterization was done via scanning electron microscopy and X-ray diffraction. The addition of 10% or more MgH2 endowed Mg with fast activation. Mg+MgH2 compacts have air resistance far superior to 100% MgH2 compacts, while keeping full capacity, fast kinetics and cyclability. The porosity after compaction was also lower for Mg+MgH2. The fast activation kinetics, together with the air resistance, allows Mg+MgH2 to be used as the starting material in Mg-based H2 storage tanks, eliminating the need for controlled atmosphere and reducing the necessity of ball milling.
The influence of MgH2 addition in Mg for application in hydrogen storage tanks
Keywords: Hidreto de magnésio; Cinética de ativação; Dispositivos para armazenamento de hidrogênio; Magnesium hydride; Activation kinetics; Hydrogen storage devices; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA DE TRANSFORMACAO